Problem relacji między nauką a techniką w kontekście społecznych uwarunkowań obu tych dziedzin - Marek Sikora (Studia Philosophica Wratislaviensia)
The article explores the relationship between science and technology in the context of their social determinants. It compares two contrasting perspectives. The first assumes the autonomy of science and the applied model of theoretical knowledge, aligning with the ideal of value-free science. The second assumes close interdependence of science and technology and the concept of value-laden science. The author argues that philosophical interpretations of relationship between science and technology increasingly support the need to consider the social determinants of both fields. This need arises from the instrumentalization of numerous scientific disciplines which, in conjunction with technology, have given rise to a novel structure of human activity—aptly termed technoscience by Gaston Bachelard. An important focus of this structure is the examination of the values and interests it serves, particularly in light of the issue of social responsibility for the outcomes produced by technoscience.